1999
DOI: 10.1046/j.1365-2133.1999.02825.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of subungual exostoses by elective day case surgery

Abstract: Twenty-one patients (11 female, 10 male: mean age 21.3 years) with subungual exostoses were treated with elective surgery under local anaesthetic in a dermatology day case theatre over a period of 8 years. Fifteen (71%) tumours affected the great toe, four (19%) affected other toes and two (10%) affected fingers. All received local excision with great care to remove all tumour residue from the terminal phalanx. Wounds were allowed to heal by secondary intention. Attention was paid to preoperative antiseptic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
0
22
0
3
Order By: Relevance
“…This approach seemed to lead to the lowest incidence of recurrence. De Berker and Langtry [9] described the use of a ronguer to adequately resect lesional tissue, whereas Davis and Cohen [8] used a curette to create a ''saucer-like defect'' into normal trabecular bone. Suga and Mukouda [34] introduced the idea that if the nail bed was intact, a fish mouth incision distally with a proximally based flap could be raised lifting the nail bed off of the lesion, thus sparing the nail.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This approach seemed to lead to the lowest incidence of recurrence. De Berker and Langtry [9] described the use of a ronguer to adequately resect lesional tissue, whereas Davis and Cohen [8] used a curette to create a ''saucer-like defect'' into normal trabecular bone. Suga and Mukouda [34] introduced the idea that if the nail bed was intact, a fish mouth incision distally with a proximally based flap could be raised lifting the nail bed off of the lesion, thus sparing the nail.…”
Section: Discussionmentioning
confidence: 99%
“…Lokiec et al [23] showed in his six-patient series that reasonable results in terms of recurrence and cosmesis can be achieved with only partial nail resection using a distally based flap, which is reattached. Recurrence was related to incomplete excision in most described cases; however, overly aggressive dissection was thought to lead to onychodsytrophy and poor cosmesis [8,9,33,34], particularly when the lesion invaded the germinal matrix [9]. In the single podiatric article included in the study, Valinsky et al [37] used local anesthesia, a laterally based incision, and a single application of intralesional corticosteroid and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations